Prevalence and spatial distribution of bovine brucellosis in San Luis and La Pampa, Argentina - Aznar, Maria Natalia (2015)
Background: Bovine brucellosis (BB) is a zoonotic disease caused by Brucella abortus. BB is endemic in Argentina, where vaccination with Brucella abortus strain 19 is compulsory for 3-to-8 month-old heifers. The objectives of this study were to quantify the prevalence of BB and to identify factors associated with its occurrence, along with the spatial distribution of the disease, in the provinces of La Pampa and San Luis. A two-stage random sampling design was used to sample 8,965 cows (3,513 in La Pampa and 5,452 in San Luis) from 451 farms (187 in La Pampa and 264 in San Luis). Results: Cow and herd prevalence were 1.8 % (95 % CI: 1.3–2.2; n = 157) and 19.7 % (95 % CI: 17.0–22.4; n = 89), respectively. Both cow-level and herd-level prevalence in La Pampa (2.4 and 26.0 %, respectively) were significantly higher than in San Luis (1.4 and 15.5 %, respectively). There were not differences between the proportions of reactive cattle compared to that obtained in a survey conducted in 2005. However, herd prevalence in La Pampa was significantly (P < 0.05) higher compared to that study. Disease was found to be spatially clustered in west La Pampa. The lower the bovine density and the calf/cow ratio, the higher odds of belonging to the cluster. Conclusions: The increase of farm prevalence in the last five years suggests that the disease is spreading and that control measures should be applied in the region. The cluster of infected farms was located in the west region of La Pampa. There, farms have lower animal densities and smaller cow/calf indices compared to the rest of the province. Although western La Pampa has more infected herds, within-farm prevalence was not higher, which suggests that the control program has been relatively successful in controlling the disease at the farm level, and/or that low animal density inherently results in low disease prevalence. Our results provide baseline information on the epidemiology of BB and its potential pattern of transmission in Argentina, which will ultimately help to improve BB control programs in the country.